Gastro Protective Effect of Madeira Vine Against Ethanol-Induced Gastric Mucosal Lesion in Rat - Horng, Chi-Ting; Chao, How-Ran; Lee, Chiu-Fang; Hsueh, Chao-Wen; Chen, Fu-An (Asian Journal of Chemistry, 2011)
Madeira vine (Anredera cordifolia (Ten.) Steenis or the synonymous name of Boussingaultia gracilis Miers var. pseudobaselloides Bailey) belongs to the family Basellaceae and has long been cultivated as a vegetable in Taiwan for dietary use. The present study investigates the effect of madeira vine on gastric mucosal protection. Ethanol-induced gastric mucosal lesions were applied to assess the gastroprotective activity of madeira vine extract powders (MVEP) in rats. Madeira vine extract powders was able to decrease significantly ulcer index of gastric mucosal lesions caused by ethanol at the dose of 250 to 1250 mg/kg. In histopathological evaluation, the ethanol-induced lesions caused moderate to severe/high acute degeneration/ necrosis with deeply ulceration and hemorrhage on the mucosal layer and submucosal edema of stomach. The amelioration of gastric mucosal lesions in histopathological observation was also found in pretreatment of madeira vine extract powders. Madeira vine extract powders possessed significant free radical scavenging activity, which could be involved in biological function of gastric mucosa protective activity. The results indicate that the madeira vine extract powders has protective effect on ethanol-induced gastric mucosal lesions in rats.